Chemical weathering as a tool for distinguishing river terraces of varying ages: a case study of the Qingyi River on the eastern Tibetan Plateau - Hua, Diwei; Jiang, Dawei; Zhang, Shimin; Ding, Rui; Chen, Yongqi (Frontiers in Earth Science, 2025)
River terraces are essential objects for studying Quaternary landforms and active tectonics. Previous researchers often identified river terraces formed in different eras by height and landmark strata. However, terraces are usually scattered in regions with severe erosion, making comparing terraces of the same level challenging. Some sedimentary analyses, including abrasion of gravels, hardness of gravels, and weathering rind thickness, have been applied to compare terraces but proved limited and not quantitative. In this study, we interpreted and surveyed the terraces of the Qingyi River, which runs through the Longmen Shan Mountain in the eastern edge of the Tibetan Plateau. A systematic approach was presented to quantitatively compare river terraces in regions of high precipitation and erosion. Firstly, we summarized the interfering factors on sedimentation, the method of collecting samples, and the choice of testing materials. Secondly, weathering indicators derived from major element testing were applied to compare terraces of different ages. Finally, we concluded the relationship between weathering degree, the terrace age, and the terrace height. The results indicated that, within the terrace age range of 300 ka, the sediments in the terrace of the Qingyi river show a linearly increasing weathering trend. It proved that the degree of chemical weathering indicated by major elements can be well applied to studying river terraces and reflect the weathering differences between terraces of different ages, solving the problem of quantitative terrace comparison. Moreover, by combining the analysis of paleoclimate data, we reconstructed the weathering mechanisms of the terraces, which are controlled by the alternation between glacial and interglacial stages.